2017
DOI: 10.3389/fmed.2017.00208
|View full text |Cite
|
Sign up to set email alerts
|

User Experience, Actual Use, and Effectiveness of an Information Communication Technology-Supported Home Exercise Program for Pre-Frail Older Adults

Abstract: ObjectiveThe main objective of this study was to investigate the use and user experience of an Information Communication Technology-supported home exercise program when offered for independent use to pre-frail older adults. Our secondary aim was to explore whether the program improved quality of life and health status compared to a control group.MethodsA cohort multiple randomized controlled trail is being performed. Physically pre-frail older adults (65–75 years) living independently at home were included and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 30 publications
2
53
0
1
Order By: Relevance
“…Further, the clinically relevant higher attrition rate in the PB group (p = .078), could be related to the two recruitment strategies, further discussed as a methodological consideration. Similar attrition rates as ours, of approximately 20%, has been reported in evaluations of other digital exercise interventions over 3-4 months [18,29,30]. For the ActiveLifestyle study the control group used a paper programme where attrition rate was 41%, slightly higher than ours [18].…”
Section: Attrition and Attitudesupporting
confidence: 81%
See 2 more Smart Citations
“…Further, the clinically relevant higher attrition rate in the PB group (p = .078), could be related to the two recruitment strategies, further discussed as a methodological consideration. Similar attrition rates as ours, of approximately 20%, has been reported in evaluations of other digital exercise interventions over 3-4 months [18,29,30]. For the ActiveLifestyle study the control group used a paper programme where attrition rate was 41%, slightly higher than ours [18].…”
Section: Attrition and Attitudesupporting
confidence: 81%
“…Considering these dissimilarities, The ActiveLifestyle study [18] indicated similar adherence as in our study: Users of the App with social features had 73% mean adherence of recommended exercise time, the App without social features had 68%, and the Paper programme (control) 54%. In a similar way Dekkeret al [29] reported 68% adherence in a 12 weeks ICT-supported self-management programme, offering an individually tailored fall prevention exercise programme. In comparison, an exergaming intervention iStoppFalls [30], reported 38% adherence as the proportion of participants reaching 1 h exercise per week during their four months intervention.…”
Section: Adherencementioning
confidence: 84%
See 1 more Smart Citation
“…Considering these dissimilarities, The ActiveLifestyle study [18] indicated similar adherence as in our study: Users of the App with social features had 73% mean adherence of recommended exercise time, the App without social features had 68%, and the Paper programme (control) 54%. In a similar way Dekkeret al [29] reported 68% adherence in a 12 weeks ICT-supported self-management programme, offering an individually tailored fall prevention exercise programme. In comparison, an exergaming intervention iStoppFalls [30], reported 38% adherence as the proportion of participants reaching 1h exercise per…”
Section: Adherencementioning
confidence: 84%
“…A digital platform that served as the data repository for a patient allowed for the following main functionalities: messaging among the key actors for a patient’s care (the patient, professional caregivers, family members, and informal caregivers), sending data to and retrieving data from a patient’s electronic medical record (EMR) and other digital applications, and the provision and processing of patient-centered surveys. A web-based service provided the Otago fall prevention program [ 19 ] (used for improving physical health [ 20 ]) through video instruction, accompanied by written instructions and a voice-over that pronounced these written instructions. Patients could indicate the difficulty they had with exercises; based upon this feedback, the service decided whether (1) they could continue to the next level of the Otago program after completing a week, (2) they would remain at the same level, or (3) they would go down a level.…”
Section: Introductionmentioning
confidence: 99%